Evolution of the Role of Seconds in the Codes of Honour by Władysław Boziewicz 1919–1927 - Byczyński, Marcin Jan (Sensus Historiae, 2024)
This article is devoted to the key persons in honour proceedings—the seconds, who were also known as honorary deputies. Through a comparative analysis of Wladyslaw Boziewicz’s codes of honour, the Polish Code of Honour (1919) and General Rules of Honorary Conduct (1927), a reconstruction will be made of the normativity of the role of seconds contained in them.. This will allow us to trace the direction of changes in Boziewicz’s reflection on the essence of the course of honour proceedings, which is contained in his codifications. Thus, one of his points of social criticism directed against the practice of honour proceedings will be revealed. The study will demonstrate how, in Boziewicz’s reflection on honour proceedings, the role of autonomous moral reflection of honour deputies and the ethical community they represent has increased in relation to the will of their principals.